Relatório de estágio técnico profissional em medicina veterinária: clínica médica de pequenos animais - Carlen, Gabriela Borges (2023)
The Professional Technical Internship (ETP) is the moment in which students have the opportunity to put into practice the theoretical teachings learned during their degree and gain experience in the professional routine of their chosen area. The ETP was carried out in the Small Animal Medical Clinic area, under the guidance of Prof. Dr. Renato do Nascimento Libardoni. The places chosen for the internship were the Veterinary Hospital of the University of Passo Fundo and Save Especialidades Veterinárias, under the supervision of veterinarians Gissele de Quadros Krahl and Jeane Beatriz Trein, respectively, from July 24th to October 23rd, 2023 , totaling 466 hours (Annexes A and B). During the ETP, it was possible to experience two different routines, one in a teaching hospital and the other in a private clinic and, in these places, several sectors were monitored, providing support to numerous veterinarians and the particularities of the medical clinic. In this way, it was possible to monitor and carry out clinical consultations, emergency care, outpatient procedures, imaging and laboratory tests, in addition to monitoring patients admitted to the first location. The clinical series and procedures performed will be presented in tables, which were subdivided into consultations, outpatient procedures, imaging exams and organic systems, specifying the location and species affected. Finally, two cases of hypothyroidism will be reported in two canines, SRD, females, castrated, aged 4 and 7 years, addressing the diagnostic and therapeutic aspects.